Parvimonasmicra bacteremia in a patient with colonic carcinoma - Muhammad Shoaib Khan; Muhammad Ishaq; mark Hinson; Bindu Potugari; Ateeq u Rehman (Babol University of Medical Sciences, 2019)
Background: Parvimonas micra is a gram-positive anaerobe and a part of the normal commensal flora of the gastrointestinal tract. Factors predisposing to anaerobic bacteremia include malignant neoplasms, periodontal disease, immune deficiencies, chronic renal insufficiency, decubitus ulcers and perforated abdominal viscus. Cases of Parvimonas bacteremia in a patient with esophageal carcinoma and in a patient following ERCP procedure have been reported but to our best knowledge no case has been reported yet in which a patient had colonic carcinoma. Case presentation: We present a rare case of a 94-year-old male who presented with chief complaint of fever and constipation. Complete blood count revealed normal white blood cell count anemia. Urinalysis came out to be unremarkable for any evidence of infection. Two blood cultures grew Parvimonas micra and Gamella morbillorum and patient was later switched to ampicillin-sulbactam as per blood culture susceptibility results. Echocardiogram came negative for any evidence of infective endocarditis. CT abdomen/pelvis showed soft tissue mass in the ascending colon just superior to the ileocecal valve (fig.1, 2). Colonoscopy showed non-obstructing eccentric mass (fig. 3). Biopsy of the mass revealed moderately differentiated adenocarcinoma. Because of lack of distant metastasis, surgical resection of the mass as definitive curative treatment was done. Conclusion: Immune deficiency is a risk factor for anaerobic bacteremia. Apart from immediately starting the patient on antibiotics, a thorough search for malignancy may be considered when a patient presents with anaerobic bacteremia, especially, when the source of infection is not known. Identifying malignancy in earliest stages may improve treatment outcome.